A demonstration of the being and attributes of God and other writings - Clarke, Samuel, 1675-1729 (Cambridge texts in the history of philosophy., 1998)
Samuel Clarke was one of the most influential Newtonian philosophers of his generation. This work, which constituted the 1704 Boyle Lectures, generated much controversy at that time.